2009
DOI: 10.1097/rli.0b013e3181a64ce9
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Control of Primary Tumor and Survival by DCE MRI During Early Therapy in Cervical Cancer

Abstract: Purpose-To assess the early predictive power of MRI perfusion and volume parameters, during early treatment of cervical cancer, for primary tumor control and disease-free-survival.Materials and Methods-Three MRI examinations were obtained in 101 patients before and during therapy (at 2-2.5 and 4-5 weeks) for serial dynamic contrast enhanced (DCE) perfusion MRI and 3-dimensional (3D) tumor volume measurement. Plateau Signal Intensity (SI) of the DCE curves for each tumor pixel of all 3 MRI examinations was gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
69
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 96 publications
(75 citation statements)
references
References 37 publications
6
69
0
Order By: Relevance
“…Significant positive correlations have been observed between parameters describing the rate or magnitude of signal enhancement and tumor pO 2 or microvascular density (24)(25)(26). Furthermore, there is increasing evidence that poor signal enhancement is correlated with poor response to radiation treatment as a consequence of hypoxia-induced radiation resistance (26)(27)(28). However, the correlations are generally weak, perhaps because the analyses were based on semiquantitative parameters derived from signal intensity curves rather than quantitative parameters calculated from Gd-DTPA concentration curves by the use of adequate pharmacokinetic models.…”
Section: Discussionmentioning
confidence: 95%
“…Significant positive correlations have been observed between parameters describing the rate or magnitude of signal enhancement and tumor pO 2 or microvascular density (24)(25)(26). Furthermore, there is increasing evidence that poor signal enhancement is correlated with poor response to radiation treatment as a consequence of hypoxia-induced radiation resistance (26)(27)(28). However, the correlations are generally weak, perhaps because the analyses were based on semiquantitative parameters derived from signal intensity curves rather than quantitative parameters calculated from Gd-DTPA concentration curves by the use of adequate pharmacokinetic models.…”
Section: Discussionmentioning
confidence: 95%
“…Studies have suggested that DCE-MRI of cervical cancer depicts functional features associated with progressive disease (5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative analysis, where some studies postulated low perfusion is the lower 10th percentile of the signalintensity curve (SI 10%) [5,39], while other considered SI 15% is more specific [5,40].…”
Section: Cancer Therapy and Oncology International Journalmentioning
confidence: 99%